THE IMPLEMENTATION OF HUMAN RESOURCE OF COMPETENCY DEVELOPMENT AT PERSONAL AND HUMAN RESOURCE AGENCY OF SUKABUMI REGENCY - ARIES TINA SUYONO; ERRY SUNARYA; DARMO H SUWIRYO (CV KULTURA DIGITAL MEDIA, 2021)
The research was motivated by the problem on the Implementation of Human Resource Competency Development Policy in Sukabumi Regency, where the policy of developing human resource competencies in Sukabumi Regency is in accordance with Regent Regulation Number 51 of 2019, that every civil servant has the same rights and opportunities to participate in Competency Development at least 20 hours of lessons/year, but in its implementation there are still obstacles so that implementation the policy is hampered. The research was aimed at analyzing the implementation of the policy and the factors that can support and inhibit the implementation of the policyfor developing human resource competencies at BKPSDM of Sukabumi Regency observed from the aspect of Communication, Resources, Disposition and Organizational Structure. The research was conducted at the Personnel and Human Resource Development Agency (BKPSDM) of Sukabumi Regency that focused on the Implementation of Human Resource Competency Policy using a qualitative approach. Techniques of collecting data applied were interviews, observations and document review. The resource persons/informants in the research were the Head of BKPSDM, Secretary, Head of PSDM Division, Head of KDP Division, Head of Planning and Evaluation Sub-Section, Head of General and Personnel Sub-Section, Civil Servant Trainer and Implementer. The Implementation of Human Resources Competency Development Policy at the BKPSDM of Sukabumi Regency has generally been carried out well viewed from the aspect of Communication, Resources, Disposition and Organizational Structure. Thus, the factors that can trigger the success of this policy are Communication and Organizational Structure aspects, while the inhibiting factors are Resources and Disposition aspects as these aspects cannot be optimized.